2015
DOI: 10.1097/md.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Parkinson Disease in Patients With Carbon Monoxide Intoxication

Abstract: The present study evaluated the association of carbon monoxide intoxication (COI) with Parkinson disease (PD).A total of 9012 adults newly diagnosed with COI were enrolled in this study as the COI cohort. The control (non-COI) cohort, comprising 36,048 participants, was matched for each COI patient according to age, sex, and the year of hospitalization. We calculated the hazard ratios (HR) and 95% confidence intervals by using a Cox proportional hazards regression model.The overall incidence of PD (per 10,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“… 39 A recent retrospective cohort study showed that victims of CO poisoning exhibited a 9.08-fold increased risk for Parkinsonism. 40 Other studies also found patients with CO poisoning are at a higher risk of developing cardiovascular complications. 33 , 41 However, there are conflicting findings about the risk of cardiovascular deaths after CO poisoning.…”
Section: Discussionmentioning
confidence: 99%
“… 39 A recent retrospective cohort study showed that victims of CO poisoning exhibited a 9.08-fold increased risk for Parkinsonism. 40 Other studies also found patients with CO poisoning are at a higher risk of developing cardiovascular complications. 33 , 41 However, there are conflicting findings about the risk of cardiovascular deaths after CO poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes, such as ubiquitin C-terminal hydrolase L1 ( UCHL1 ) [ 71 ], α-synuclein ( SNCA ) [ 72 ], leucine-rich repeat kinase 2 ( LRRK2 ) [ 73 ], Parkin RBR E3 ubiquitin-protein ligase ( Parkin ) [ 74 ], PTEN-induced kinase 1 ( PINK1 ) [ 74 ], protein deglycase ( DJ-1 ) [ 75 ], and glucocerebrosidase ( GBA ) [ 76 ] can result in the development of PD. Several environmental factors, like exposure to pesticides (rotenone, and paraquat) [ 77 ], methanol (CH 3 OH) [ 78 ], injury to the head [ 79 ], and poisoning of carbon monoxide (CO) [ 80 ] are thought to be associated with the development of PD.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…The patient was initially treated with 100% normobaricoxygen, and then intubated and mechanically ventilated, the most common treatment for CO toxicity [24]. Neurological injury is well documented after CO toxicity, with reports of patients that range from transient neurologic deficits to chronic debilitating diseases such as Parkinson's disease and multiple sclerosis after exposure to CO. [17,18,27]. The patient presented here suffered from neurological outcomes, where we were able to, for the first time ever, uncover potential mechanisms for neurological outcomes using a multi-time point, multi-omics strategy.…”
Section: Introductionmentioning
confidence: 93%